Long-Term Maintenance and Meiotic Entry of Early Germ Cells in Murine Testicular Organoids Functionalized by 3D Printed Scaffolds and Air-Medium Interface Cultivation - Richer, Guillaume; Hobbs, Robin M.; Loveland, Katherine L.; Goossens, Ellen; Baert, Yoni (Frontiers in Physiology, 2021)
Short-term germ cell survival and central tissue degeneration limit organoid cultures. Here, testicular organoids (TOs) were generated from two different mouse strains in 3D printed one-layer scaffolds (1LS) at the air-medium interface displaying tubule-like structures and Leydig cell functionality supporting long-term survival and differentiation of germ cells to the meiotic phase. Chimeric TOs, consisting of a mixture of primary testicular cells and EGFP+ germline stem (GS) cells, were cultured in 2LSs for better entrapment. They showed an improved spheroidal morphology consisting of one intact tubule-like structure and surrounding interstitium, representing the functional unit of a testis. However, GS cells did not survive long-term culture. Consequently, further optimization of the culture medium is required to enhance the maintenance and differentiation of germ cells. The opportunities TOs offer to manipulate somatic and germ cells through genetic modifications, inclusion or exclusion, are essential for the study of male infertility and the search for potential therapies.